1996
DOI: 10.1111/j.1399-3054.1996.tb00682.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in non‐structural carbohydrates in olive (Olea europaea) leaves during root zone salinity stress

Abstract: Self‐rooted olive (Olea europaea L.) plants were grown in hydroponics at various NaCl concentrations (from 0 to 200mM) for 28 to 32 days followed by 28 to 30 days of relief from salinity over two growing seasons. Olive leaves accumulated both glucose and mannitol during the period of salinity stress. The concentrations of fructose, myo‐inositol, galactose, galactinol, sucrose, raffinose, and stachyose were not significantly affected by salinity. Starch content was decreased by salinity. The mannitol/glucose an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
43
3

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(52 citation statements)
references
References 28 publications
6
43
3
Order By: Relevance
“…At the maximum level of water deficit, mannitol content was 1.3 times higher in leaves of SP than in CP, confirming that this alditol plays a key role in osmotic adjustment of leaf tissues during water deficit. The increased foliar content of mannitol in olive leaves could be related to an increased activity of mannose-6-phosphate reductase (M6PR) and a decreased activity of mannitol dehydrogenase (MDH), which are the two key enzymes involved in the biosynthesis and catabolism of this sugar (Tattini et al 1996). In thin roots (c) during the experimental period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the maximum level of water deficit, mannitol content was 1.3 times higher in leaves of SP than in CP, confirming that this alditol plays a key role in osmotic adjustment of leaf tissues during water deficit. The increased foliar content of mannitol in olive leaves could be related to an increased activity of mannose-6-phosphate reductase (M6PR) and a decreased activity of mannitol dehydrogenase (MDH), which are the two key enzymes involved in the biosynthesis and catabolism of this sugar (Tattini et al 1996). In thin roots (c) during the experimental period.…”
Section: Discussionmentioning
confidence: 99%
“…Among fruit tree species, olive tree is able to tolerate a broad range of adverse environmental factors, including the low availability of water in soil (Bacelar et al 2007), salinity (Tattini et al 1996), chilling and high temperature stress (Bongi and Long 1987) and high irradiance levels (Sofo et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, under elevated CO 2 , stronger CO 2 diffusion gradients and increased WUE i would have mitigated these effects, at least within the salinity range observed (4-18 ppt). Furthermore, it is possible that an enhanced availability of non-structural carbohydrates under elevated CO 2 (Cheng, Moore, & Seemann, 1998) provided an energy subsidy for P. australis to mitigate the osmotic stress associated with salinity (Tattini, Gucci, Romani, Baldi, & Everard, 1996).…”
Section: Salinity (Ppt)mentioning
confidence: 99%
“…Haitao et al (2013) demonstrated that arginase expression modulates abiotic stress tolerance in Arabidopsis. It was suggested by Tattini et al (1996) that in olive leaves, mannitol and glucose play an active role in the osmotic adaptation of plants to salinity. These studies clearly demonstrate that the protein metabolism and carbohydrate metabolism play very important roles in the stress response.…”
Section: Introductionmentioning
confidence: 99%